THE USE OF OCTALAND FLASHCARD APPS AS MEDIA IN TEACHING VOCABULARY TO YOUNG LEARNERS (A Qualitative Research at Young Learners EFL Classroom) - Novtiani, Nurul (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2022)
Vocabulary is list of words with their meanings, especially for learning a foreign language (Richard, 2002:4). In learning vocabulary, media can be used to transmit the information from the teacher to the students. Conventional flashcard as a media is commonly used in the classroom. In this case, Octaland Flashcard Apps can become alternative media for teaching vocabulary to young learners. This study aims 1) to illustrate the process of teaching vocabulary to young learners by using Octaland Flashcard Apps; 2) to investigate the strengths and weaknesses of the use Octaland Flashcard Apps as media in teaching vocabulary to young learners; and 3) to investigate young learners responses toward the use of Octaland Flashcard Apps in Teaching Vocabulary. This research was qualitative research conducted in SD Negeri Jamaras Cianjur at the fourth grade elementary school. The instrument used observation, interview, and questionnaire. The result of analysis shows that in implementing Octaland Flashcard Apps the teacher divided the activities into three: Pre-teaching, While-teaching and Post-teaching. There were several strengths of using this apps: the apps made young learners happy and enthusiastic, the apps produced native speaker sound, the apps was also added by cheerful music background, and this apps could be multifunction media. However, there were some weaknesses of the apps such as this apps needed good internet connection, this apps needed well-lightening to scan the flashcard and the use of this apps made the students a little bored because of waiting their turn to scan the Octaland Flashcard Apps. Regarding young learners response toward the use of Octaland Flashcard Apps in teaching vocabulary, the learners admitted that it created fun and interesting learning for them because they could learn and play at the same time, the characters on the flashcards could be alive as real object, and it was easier for them to memorize and comprehend English vocabulary. However, the learners also stated that there were some words that difficult to spell and the learning was a little boring because they had to wait for their turn to scan the flashcard. Furthermore, the students felt that the learning needed more opportunities and various cards, and they wanted to continually use this Octaland Flashcard Apps for their learning.